TEACHING ARCHITECTURE, LEARNING TEACHING: A CRITICAL EXPERIENCE IN BRAZILIAN GRADUATE EDUCATION - Gurgel, Ana Paula Campos (Seven Editora, 2025)
This article presents a critical analysis of teacher education in Architecture and Urbanism in Brazil, based on the experience of the course “Pedagogies in Architecture and Urbanism”, offered in the Graduate Program of FAU-UnB in 2025. Starting from the recognition that teaching in the field has historically been treated as a natural extension of professional practice—rather than as a specific field of knowledge—the study problematizes the absence of structured pedagogical training in graduate programs, as well as the effects of this gap on higher education. The analyzed course was designed to address this shortcoming by integrating theoretical foundations of education, active pedagogical practices, and spaces for reflection on the political, ethical, and social role of the Architecture professor. The formative trajectory included dialogical classes, workshops, seminars, analyses of regulatory documents, methodological experimentation, and formative assessment processes. The heterogeneous composition of the class, with students from different academic levels and trajectories, fostered the circulation of diverse experiences and broadened the debate on contemporary challenges of teaching, especially those related to critical mediation, active listening, and the role of the design studio as a learning space. Evaluations indicate high levels of engagement and recognition of the course as a safe and stimulating environment for discussing the tensions that permeate Architecture education in Brazil. The results reveal both potentialities and structural limitations, such as reduced workload, institutional fragility of teacher education, and the persistence of traditional models. It is concluded that, although isolated initiatives are essential, there is a need to advance toward institutional policies that place pedagogy at the center of the training of architect-educators.DOI: https://doi.org/10.56238/sevened2025.038-083